العوامل المؤثرة في الاستثمار الأجنبي المباشر في الجمهورية العربية السورية - الحسين, محمد; اليوسف, جمال; صقر, منال سليمان (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يهدف البحث إلى دراسة العوامل المؤثرة في الاستثمار الأجنبي المباشر من خلال صياغة مدخل كمي يمكن اعتماده, ويتحدد من خلاله تأثير العوامل الداخلية والخارجية في الاستثمار الأجنبي المباشر. وقد اعتمدت الباحثة على المنهج الاستقرائي الرياضي لبحوث العمليات باعتماد أسلوب التحليل العاملي. وتوصلت بعد الدراسة والتحليل إلى النتائج الآتية: 1- يختلف حجم مشاريع الاستثمار الأجنبي في سورية باختلاف القطاعات الاقتصادية, إذ تتركز في قطاعات الصناعات التحويلية, والقطاع المالي, والنقل والمواصلات, والاتصالات بالدرجة الأولى بالموازنة مع القطاعات الأخرى. 2- يختلف حجم مشاريع الاستثمار الأجنبي في سورية باختلاف المناطق الجغرافية, إذ تتركز في المنطقتين الجنوبية والشمالية بالموازنة مع المناطق الأخرى. 3- تُوصل إلى نموذج كمي لإدارة الاستثمار الأجنبي في سورية يراعي المتغيرات المدروسة, ويحدد تأثيراتها السلبية أو الإيجابية, ويصنفها حسب أهميتها النسبية. The research aims at studying the factors affecting foreign direct investment through the formulation of an adoptable quantitative approach, and through which the impact of internal and external factors on foreign direct investment can be determined. The researcher relied on inductive mathematical approach to operations research by adopting factor analysis method. After the study and analysis, we come up with following results: 1- The volume of foreign investment projects in Syria varies with the differences in economic sectors, where they are mainly found in the sectors of manufacturing, finance, transportation and communications compared with other sectors. 2 – The volume of foreign investment projects in Syria varies with the differentces in geographical areas, where they are are mainly found in the southern and northern regions compared with other regions. 3 – the study comes up with a quantitative model for the management of foreign investment in Syria that takes into account variables studied and determines whether they affect, positively or negatively and categorizes them according to their relative importance.